2017
DOI: 10.1016/j.jcomdis.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual statistical learning over one week in child speech production

Abstract: What cognitive mechanisms account for the trajectory of speech sound development, in particular, gradually increasing accuracy during childhood? An intriguing potential contributor is statistical learning, a type of learning that has been studied frequently in infant perception but less often in child speech production. To assess the relevance of statistical learning to developing speech accuracy, we carried out a statistical learning experiment with four- and five-year-olds in which statistical learning was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(114 reference statements)
2
7
0
Order By: Relevance
“…Accuracy was marginally lower in the low experimental frequency condition for the phonotactic learning first data (β = -.08, SE = .05, t = -1.66, p = .097); accuracy was significantly higher in the low experimental frequency condition for the phonotactic learning second data (β = .29, SE = .04, t = 6.51, p < .001). The results for the phonotactic learning second condition are surprising because high experimental frequency has typically been reported to increase children's production accuracy relative to low experimental frequency (for example, Plante et al, 2011;Richtsmeier et al, 2009;Richtsmeier & Goffman, 2017;Richtsmeier & Good, 2018).…”
Section: Phonotactics Experimentsmentioning
confidence: 89%
See 2 more Smart Citations
“…Accuracy was marginally lower in the low experimental frequency condition for the phonotactic learning first data (β = -.08, SE = .05, t = -1.66, p = .097); accuracy was significantly higher in the low experimental frequency condition for the phonotactic learning second data (β = .29, SE = .04, t = 6.51, p < .001). The results for the phonotactic learning second condition are surprising because high experimental frequency has typically been reported to increase children's production accuracy relative to low experimental frequency (for example, Plante et al, 2011;Richtsmeier et al, 2009;Richtsmeier & Goffman, 2017;Richtsmeier & Good, 2018).…”
Section: Phonotactics Experimentsmentioning
confidence: 89%
“…The four target consonant sequences were chosen because consonant sequences are relatively difficult, making it likely that children would sometimes produce them in error, and learning could be measured. We note that data from the phonotactics experiment-when that experiment was completed firstare reported in Richtsmeier and Goffman (2017). All other data have not been reported elsewhere.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The targets appeared medially in nonwords (referred to hereafter to as items) with a CVCCVC shape and with stress on the initial CVC syllable. Although there is some evidence that item-medial consonant sequences are more difficult to learn than word-initial and word-final consonants (Endress & Mehler, 2010), other studies have confirmed that participants are sensitive to the experimental frequencies of these sequences (Richtsmeier, 2011(Richtsmeier, , 2016Richtsmeier & Goffman, 2017). Recordings of the items for this study were culled from those latter studies.…”
Section: Methodsmentioning
confidence: 99%
“…Participants heard items from 7-10 talkers, with the number of talkers depending on the list, and with 13 different talkers being used across all lists. In statistical learning research, talker variability is often beneficial (Bulgarelli & Weiss, 2018;Plante, Bahl, Vance, & Gerken, 2011;Richtsmeier, Gerken, Goffman, & Hogan, 2009;Richtsmeier & Goffman, 2017). However, the benefits are small, and talkers beyond the first two or three do not appear to provide an additional benefit (Richtsmeier & Moore, In preparation).…”
Section: Methodsmentioning
confidence: 99%